How training is encouraging mothers to deliver in health facilities in Ulang, South Sudan - Panom Puok Duoth Kier (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2021)
In South Sudan, health facility delivery coverage is very low despite the presence of health facilities with staff that can conduct deliveries. Some factors like inaccessibility, insecurity, low knowledge of benefits of health facility delivery, poor services, financial challenges, family influence and cultural practices might be some of the reasons that prevent some mothers from delivering in the health facilities. This paper describes how UNICEF with other partners has started training master trainers with Basic Emergency Obstetrics and New Born Care modules in Greater Upper Nile, and includes a case of one mother who benefited from the training.